Pensions: A Complex Landscape - Frank Eich; Amarendra Swarup (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2008)
Pension reforms have been high on the political agenda in many developed countries over recent years and pension issues have been discussed intensely in the public as a result. In recent years, much effort has been devoted to make state, public and private pension systems fiscally more sustainable in the light of demographic change. In many developed countries, this has been achieved - at least ex ante - by encouraging greater private sector and personal involvement. Equally, many governments in emerging economies and developing countries have been pursuing their own pension reform agendas. Nevertheless, despite this spotlight on pensions, many important facets remain badly understood and need to be discussed in greater detail. Most observers would agree that societies have not yet reached the end of the reform process and that dealing with pensions may always remain “work in progress” as new information becomes available – such as on trends in life expectancy - and as societies evolve. Furthermore, additional effort will most likely be required to ensure that the desired outcomes will eventually materialise. The purpose of this note is to ask some of the key questions that could inform future research into pensions. The general issue under consideration is not new. How to structure the future provision of pensions, taking into account wider economic, demographic and societal considerations at home and abroad? Governments around the world have been dealing with this issue for years, international organisations, think tanks and trade unions have given advice, and universities have provided valuable analysis. Societies have been dealing with this in their own particular ways, reflecting differences in cultural and historical backgrounds, and economic and demographic circumstances. Despite the closer integration of the world economy, in most countries, this issue has been treated as a domestic issue. The private sector has played its own important part in many countries by offering occupational pensions or by offering financial products, helping both the sponsors of pensions as well as individuals prepare financially for retirement. The fact that governments across the world have reduced ex ante their future fiscal burden by encouraging greater private sector and personal involvement does not mean though that this will also be ex post the eventual outcome. For the desired outcome to materialise, the private sector and personal involvement must develop as intended. Experience from around the world shows that this has not always been the case, requiring frequent and potentially costly policy changes and putting additional burdens on individuals and businesses alike. The complex interactions between fiscal policy and pension savings also play a role for both – an area touched on briefly later in this essay when we examine the role of tax relief. In a number of developed countries, for example, defined benefit pension plans have been closed to new members as scheme sponsors face increasing liabilities in the light of ever higher life expectancy and find the resulting regulatory funding requirements increasingly unaffordable. Does this trend require adjustments elsewhere in a country's pension arrangements? Will today's structures deliver the desired outcomes or do participants such as governments and financial markets need to innovate? There are a number of ways the issue of future pension provision could be approached. For example, one might want to think about the issue in terms of desirable objectives for a pension system such as: Efficiency (static and dynamic) Equity (fairness) Affordability and sustainability (both financial and social) These objectives could then be used as a core set of overlapping “lenses” when looking at the issue of future pension provision, though other “lenses” are feasible too. Importantly, as we shall demonstrate, these “lenses” can be used to study pensions simultaneously at a range of scales from large “big picture” macroeconomic themes such as political uncertainty to subtler, smaller scale but equally important issues such as the management of assets and liabilities for an individual pension fund. There is also the issue of credibility – in particular, political consistency – which cuts across all the lenses under consideration here and is touched on later in the essay. However, before doing so, this note provides some background on pension arrangements in developed and developing countries.
Keywords: 330; Financial markets; Economics; Savings; Pension systems; Labour market; Government policy